Toe nail malalignment associated with hallux valgus. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Case report. A 12-year-old girl was first observed due to the presence of nail disorders of both halluces from many years. The family history showed hallux valgus in her 40-year-old mother. The nail problem of the patient had got evident at the age of 1 year with discoloration and thickness of both the toenails, which also repeatedly had fallen and regrown. The girl had often been treated with oral and topical antifungal with no avail, despite the mycological examination had been repeatedly negative. Physical examination (Fig. 1) showed malaligned, greenish-yellow toenails, with evident transverse fracture (onychomadesis) in the middle. It also highlighted initial valgus of the big toe, for which the patient was sent to the orthopedic. These features led to the final diagnosis of big toe nail malalignment associated with hallux valgus and to recommend realignment surgery of the nail.